Harmonisasi Kehidupan Beragama Masyarakat Bulurejo, Kabupaten Banyuwangi: Harmonization of Religious Life in the Bulurejo Community, Banyuwangi Regency - Khairunnisa Chyntia (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2025)
This study aims to describe and analyze the harmonization of religious life in Bulurejo Village, Banyuwangi Regency, as an example of a multicultural community's success in building harmony. Bulurejo is a village with religious diversity consisting of Islam, Christianity, and Hinduism, but it is still able to maintain social stability through daily interactions, local traditions, and cultural wisdom values. This study uses a qualitative approach through observation, in-depth interviews with religious and community leaders, and documentation studies. The results show that harmony is created through social interactions such as mutual assistance, rewang, and interfaith participation in social and religious activities. In addition, the traditions of Suroan and Bersih Desa serve as neutral cultural media that bring all residents together in a form of collective gratitude while strengthening social solidarity. Internal flexibility among congregations in five different churches also demonstrates a high level of tolerance in religious life. Based on Herbert Blumer's symbolic interaction theory, harmony in Bulurejo is formed through a process of meaning creation, repeated interaction, and positive interpretation of social symbols. This study confirms that harmony in Bulurejo is not only formal in nature but grows from social and cultural practices that continue to be maintained as important capital in strengthening Indonesia's diversity.